Supervisor Behaviours that Facilitate Training Transfer - Lancaster, S.; Di Milia, L.; Cameron, Roslyn (Emerald Group Publishing Limited, 2013)
Purpose: The purpose of this paper is to describe the supervisor behaviours that employees found to be helpful and unhelpful in facilitating training transfer. The study aims to provide rich qualitative data from the employee's perspective. Design/methodology/approach: This study utilises a cross-sectional design. A case study and a qualitative interpretivist approach were used to interpret the employee's responses. In total 24 semi-structured interviews were conducted and responses were analysed with the aid of NVivo. Findings: The results suggested what supervisors did prior to, during and after course attendance was critical to training transfer. Supportive behaviours prior to the course included motivating, encouraging and setting expectations. Practical support provided during the course signalled the value that the supervisor placed on the course. Meetings held after the course provided the best opportunity to support transfer. Transfer was maximised when participants experienced a positive role model and when supervisors showed interest in their experience of the course, encouraged and sponsored new initiatives, and involved them in decision-making. The main perceived hindrances to training transfer were culture, policies and a lack of encouragement. Originality/value: This is a qualitative study in a field of inquiry dominated by quantitative approaches. The results highlight the employee's perspective concerning what they found to assist in training transfer. This methodology is rarely evidenced in the extant literature.